2019
DOI: 10.1212/cpj.0000000000000634
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities caring for neurology outpatients across language differences

Abstract: BackgroundWith over 66 million Americans who speak over 350 languages other than English at home, we sought to examine attitudes and behaviors of neurology clinicians and staff when communicating across language differences.MethodsWe conducted an electronic-enabled cross-sectional survey of clinicians and patient services coordinators working at an academic neurology outpatient clinic. Questions focused on professional medical interpreter (PMI) services usage, satisfaction, and perceived barriers to utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Hence, they have reduced confidence in interaction with PMIs, who in turn are scarce. 3,8 A study from New Jersey examined whether availability of in-person professional interpreter services during emergency department visits affected the satisfaction of patients with LEP and their health care clinicians. Regression-adjusted results indicated that 96% of patients and their clinicians were satisfied when an in-person interpreter was available compared with when other forms of interpretation were used.…”
Section: Interpreter Servicesmentioning
confidence: 99%
“…Hence, they have reduced confidence in interaction with PMIs, who in turn are scarce. 3,8 A study from New Jersey examined whether availability of in-person professional interpreter services during emergency department visits affected the satisfaction of patients with LEP and their health care clinicians. Regression-adjusted results indicated that 96% of patients and their clinicians were satisfied when an in-person interpreter was available compared with when other forms of interpretation were used.…”
Section: Interpreter Servicesmentioning
confidence: 99%